FACTORS AFFECTING HOUSING PRICES IN MALAYSIA: ANALYSIS OF THE SUPPLY SIDE - Olanrewaju, Abdul Lateef; Lim, Xin Ying; Tan, Seong Yeow; Lee, Jia En; Adnan, Hamimah (PLANNING MALAYSIA, 2018)
Buying a house is a major decision that homebuyers will make because expenditure on homeownership has an influence on the homeowner’s quality of life. The housing price also influence developers’ revenues and profit margins. Developers produce houses to make profits, however, with the increase in housing prices, homeownership rate and developers’ profit performance will be affected. This study examines the reasons why housing prices are increasing in spite of the government’s ‘cooling’ measures. Through a cross-sectional survey questionnaire, comprising 24 causes and 115 members of the housing developers and designers teams, 13 influential factors to the increase in housing prices were found. Additionally, the participants were also inquired on the five most influential factors causing the increase in housing prices. The factors include the shortage of materials, quality of materials, strategic factors, housing location and availability of transportation system. The results of the study are useful to developers, homebuyers and policymakers towards reducing housing prices.